Arabic Language Program Management: A Case Study at Al-Kindi Association - Arzaqi, Muhammad Aulia Wildanihza; Falah, Muhammad Fajrul (JURNAL IJ-ATL, 2024)
Managing Arabic language instruction for non-native speakers requires strategies that integrate pedagogical clarity, cultural sensitivity, and adaptive learning tools. This study aims to examine the management practices applied in the Arabic program at Al-Kindi Association and how these practices contribute to effective language acquisition. The background of this research stems from the increasing demand for structured Arabic education programs that meet both academic and practical communication needs of diverse learners. The study emphasizes three core areas of program management: curriculum design, instructional methods, and evaluation systems. Using a qualitative descriptive approach, data were gathered through in-depth interviews with program coordinators and instructors, classroom observations, and documentation of learning materials and evaluation instruments. The findings reveal that the program’s management is rooted in learner-centered planning, with a focus on communicative competence, blended learning, and reflective evaluation. Key strategies such as the integration of digital platforms, peer-based teaching, and culturally immersive learning activities contribute significantly to learner motivation and achievement. These findings suggest that a holistic and adaptive management model can enhance the quality and sustainability of Arabic language education for non-native speakers.